Soil physical properties and water dynamics under contrasting management regimes at the Morrow Plots - Obour, P.B.; Xia, Y.; Ugarte, C.M.; Grift, T.E.; Wander, M.M. (Soil & Tillage Research, 2024)
This study investigated changes in soil physical quality and water dynamics arising from continuous cropping at the Morrow Plots, the oldest agricultural experiment in North America. The objectives were to examine the effects of continuous cultivation on soil water retention and determine the optimum water content for tillage (θOPT) in a prime agricultural soil. Soil samples collected at 0–5, 5–10, and 10–15 cm depths were used to measure bulk density and water retention using the HyProp 2 and WP4-T Dewpoint Potentiometer. Soil organic carbon (SOC) and soil penetration resistance (PR) were measured to a depth of 15 cm. The soil water retention data were fitted with the Dexter double exponential and van Genuchten models. Neither model consistently fitted all the water retention data across the different management practices. The corn-oat-hay (COH) rotation generally reduced soil bulk density within the 0–15 cm depth by an average of 9 % and PR by 21 % compared to the continuous corn (CC) treatment. The COH rotation slightly increased topsoil water-holding capacity (0–15 cm), although trends varied with fertility regimes. The θOPT for the COH and CC estimated by the van Genuchten model was generally wetter than the water content at field capacity (θFC). In contrast, the θOPT estimated by the Dexter model was slightly drier than θFC. Despite limitations due to the lack of true replicates and the small sample size at the Morrow Plots, this research underscores the long-term impact of crop rotation on soil hydraulic properties in prime agricultural soils.
Research Article
Keywords: Bulk density; Crop rotation; Fertilization regimes; Optimum water content for tillage; Penetration resistance; Soil water retention